A field study investigating the effectiveness of vat milk controls by qPCR for the prevention of undesired propionic acid fermentation in Sbrinz PDO cheese. (February 2018) - Turgay, Meral; Schaeren, Walter; Graber, Hans Ulrich; Wagner, Elvira; Amrein, Rudolf; Bütikofer, Ueli; Wechsler, Daniel
Abstract: The accurate monitoring of propionic acid bacteria (PAB) in cheese milk is of high importance since they can provoke undesired propionic acid fermentation during the ripening of unpasteurised milk cheeses. In the present study, we analysed 560 vat milk samples and 40 corresponding Sbrinz cheeses to evaluate the effectiveness of qPCR based controls of vat milks for the prevention of undesired propionic acid fermentation in Sbrinz PDO cheese. Two qPCR assays were used: one for the thermoduric species Propionibacterium freudenreichii and the other for the combined detection of the thermosensitive species Propionibacterium thoenii, Propionibacterium jensenii, and Propionibacterium acidipropionici . Thermoduric and thermosensitive PAB were detected in 35% and 19%, respectively, of the vat milks. However, in defective Sbrinz cheeses with propionic acid fermentation P. freudenreichii was the predominant species, indicating that low contaminations of thermosensitive PAB in vat milk do not present a risk in the manufacture of hard cooked cheeses.